Optimization of East Java Propolis Extraction as Anti SARS-Cov-2 by Molecular Docking Study (Faculty of Animal Science Universitas Brawijaya, 2022)
The purpose of this research is to obtain the optimum propolis extraction method using microwave extraction so as to produce anti-SARS CoV-2 compounds. The research method used was experimental with a completely randomized factorial design consisting of 2 factors namely extraction time and power level, 9 treatments and 3 replications. The extraction using microwave assisted extraction was carried out according to treatment factors, namely low power level (A1), medium (A2), high (A3) and the length of treatment time was 10 minutes (B1), 20 minutes (B2), and 30 minutes (B3). The results of statistical analysis showed that the interaction between the two had a high significant effect (p<0.01) on the alkaloid content which is ranged from 0.665 to 1.452 mg/g and had no effect on color L*a*b* and antioxidant activity which is ranged from 1.533 to 1.553. The percentage of hexadecane in East Java propolis extract was 0.280 %, octadecane was 0.775%, and pentacosane was 6.716%. The results of druglikeness analysis showed that hexadecane, octadecane and pentacosane compounds had potential as antivirals with a probability to be active value of 0.68. The binding affinity value produced by enzalutamide as a native ligand is -6.7 kcal/mol while the highest inhibitory value is octadecane and pentacosane of -5.9 kcal/mol and followed by hexadecane at -5.8 kcal/mol. The conclusion of this research is that the most optimal extraction method using microwave assisted extraction is done with a medium microwave power level for 30 minutes in terms of the alkaloid content and antioxidant activity produced. This method is able to produce extracts with good antiviral bioactive components, although the binding affinity has not been able to exceed the native ligand's ability in terms of the molecular docking approach.